Pearls of the past (Münster)
xxi, 916 sayfa
Keywords: “Almost four dozen articles are devoted to the Near Eastern Archaeologist Frances Pinnock (La Sapienza, Roma). In accordance with her special field of research several focus on the archaeology of and excavations in ancient Syria, especially Ebla / Tell Mardikh. Further contributions also explore and discuss excavations, objects, and questions of cultural history of Anatolia, Lebanon, Jordan, Palestine (Jericho), and Mesopotamia“ --